The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.pscychresns.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The association of sleep and physical activity with integrity of white matter microstructure in bipolar disorder patients and healthy controls

Abstract: We investigate how the sleep disruptions and irregular physical activity levels that are prominent features of bipolar disorder (BD) relate to white matter microstructure in patients and controls. Diffusion tension imaging (DTI) and 14-day actigraphy recordings were obtained in 51 BD I patients and 55 age-and-gender-matched healthy controls. Tract-based spatial statistics (TBSS) was used for voxelwise analysis of the association between fractional anisotropy (FA) and sleep and activity characteristics in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 65 publications
0
11
0
1
Order By: Relevance
“…Regionally, poor sleep has consistently been related with lower WM integrity in the internal capsule, corpus callosum, forceps minor, and superior longitudinal fasciculus (Baillet et al., 2017, Sexton et al., 2017)—tracts that are also affected in insomnia. The effects of poor sleep on WM integrity are similar during middle age, with shorter sleep duration being related to lower FA (Verkooijen et al., 2017, Yaffe et al., 2016) and higher MD in widespread areas (Yaffe et al., 2016). Interestingly, widespread decreases in FA have been detected after 1 day of sleep deprivation in young adults, indicating that poor sleep may impact on WM microstructure (Elvsåshagen et al., 2015).…”
Section: Modifiable Factors and Wm Microstructurementioning
confidence: 97%
See 1 more Smart Citation
“…Regionally, poor sleep has consistently been related with lower WM integrity in the internal capsule, corpus callosum, forceps minor, and superior longitudinal fasciculus (Baillet et al., 2017, Sexton et al., 2017)—tracts that are also affected in insomnia. The effects of poor sleep on WM integrity are similar during middle age, with shorter sleep duration being related to lower FA (Verkooijen et al., 2017, Yaffe et al., 2016) and higher MD in widespread areas (Yaffe et al., 2016). Interestingly, widespread decreases in FA have been detected after 1 day of sleep deprivation in young adults, indicating that poor sleep may impact on WM microstructure (Elvsåshagen et al., 2015).…”
Section: Modifiable Factors and Wm Microstructurementioning
confidence: 97%
“…A recent systematic review indicated higher FA in physical active or fit individuals, with less, but consistent, evidence for either lower or unchanged diffusivity values (MD, RD, AxD) (Sexton et al., 2016). Regionally, higher levels of physical activity or fitness have been related to higher FA in many tracts, but most consistently in the corpus callosum (Burzynska et al., 2015, Hayes et al., 2015, Oberlin et al., 2016, Tian et al., 2015, Verkooijen et al., 2017), corona radiata (Oberlin et al., 2016, Smith et al., 2016, Verkooijen et al., 2017), fornix (Oberlin et al., 2016), internal capsule (Burzynska et al., 2015, Oberlin et al., 2016, Smith et al., 2016), cingulum (Oberlin et al., 2016, Tian et al., 2015), and several association tracts, among them the superior longitudinal (Oberlin et al., 2016, Tian et al., 2015), inferior fronto-occipital (Tian et al., 2015), and uncinate fasciculi (Burzynska et al., 2015). Diffusivity findings are less clear, with some studies showing that RD reductions accompany FA increases (Smith et al., 2016) and others reporting lower MD or RD in areas unrelated to FA changes (Gons et al., 2013).…”
Section: Modifiable Factors and Wm Microstructurementioning
confidence: 99%
“…While it is currently unknown which neurotransmitter receptors mediate iSP, these findings indicate that chronic exercise increases transcallosal inhibition. Chronic exercise improves white matter integrity in the corpus callosum (Johnson and others 2012; Oberlin and others 2016; Svatkova and others 2015; Verkooijen and others 2017), likely contributing to the increases in iSP.…”
Section: Model Of Neuroplasticity Induced By Chronic Aerobic Exercisementioning
confidence: 99%
“…Study of associations between actigraphy with cognitive and neuroimaging measures can help to uncover the neurobehavioral mechanisms that contribute to mood and rest patterns. There is growing evidence that disturbances in the rest period in BD, involving both the onset and duration of sleep, are associated with impaired white matter microstructure, as measured by lower fractional anisotropy, particularly in the genu and body of the corpus collosum and corona radiata ( 93 ). Additionally, disturbances in SE and abnormal activity rhythms in euthymic BD were found to be associated with increased functional connectivity in the dorsolateral prefrontal cortex, implicated in working memory processes ( 94 ).…”
Section: Resultsmentioning
confidence: 99%